HLA-B60 and HLA-DR4 alleles in Javanese children with steroid-sensitive primary nephrotic syndrome - M P Damanik (Indonesian Pediatric Society, 2006)
Background Steroid-sensitive nephrotic syndrome (SSNS) ofchildren is associated with several human leucocyte antigen (HLA)class I and class II.Objective To investigate the association between HLA-B60 andHLA-DR4 alleles and primary nephrotic syndrome (PNS) inJavanese children.Methods A case control study was conducted on 47 Javanesechildren with PNS who were typed for HLA-B60 and HLA-DR4 al-leles, using DNA sequence specific oligonucleotide probe (SSOP)as control sample, 47 healthy children were also typed for thoseHLA antigens using the same technique.Results Compared with control group, children with PNS had higherfrequency of both HLA-B60 (23.32% vs 4.3%; OR=6.85 [CI=1.32-35.65]; P<0.01) and HLA-DR4 (40.0% vs 2.1%; OR=30.67 [CI:3.71-253.33]; P<0.0002). There was association between HLA and PNSwith SSNS in children.Conclusion The strong association between PNS and HLA anti-gen support the immunogenetic background of the disease, whichseems to be stronger in young children with SSNS.